Prevalence and predictors of post stroke depression among elderly stroke survivors - Santos, Emanuella Barros dos; Rodrigues, Rosalina Aparecida Partezani; Pontes-Neto, Octávio Marques (Arquivos de Neuro-Psiquiatria, 2016)
Objective To identify the prevalence of post stroke depression (PSD) and their socio-demographic and clinical predictors among elderly stroke survivors after hospital discharge to home.Methods In this cross-sectional study, 90 elderly stroke survivors were evaluated 14 days after hospital discharge with the following scales: National Institutes of Health Stroke Scale, Functional Independence Measure, and Geriatric Depression Scale – 15 items (GDS-15). PSD was defined as a score > 5 on GDS-15. After univariate analyses, a multivariate logistic regression model was built to identify independent predictors of PSD.Results Fourteen days after hospital discharge, 27.7% (95%CI 18.1 to 37.2) of elderly stroke survivors had PSD. Functional dependence was the only independent predictor of PSD (OR: 1.04 95%CI: 1.01 to 1.09; p = 0.02).Conclusion After stroke, depressive symptoms are common among elderly survivors. The degree of functional dependency is the main predictor of PSD among elderly stroke patients in Brazil.
Keywords: stroke; depression; aged; activities of daily living